Spectral properties of macro-tunnel covers and their relation with growth and yield of poblano pepper (Capsicum annuum L.). - Zermeño González, Alejandro; Marroquín Morales, José Ángel; Melendres Alvarez, Aaron Isain; Ramírez Rodríguez, Homero; Cadena Zapata, Martín; Campos Magaña, Santos Gabriel (REVISTA TERRA LATINOAMERICANA, 2019)
With protected agriculture, plants are sheltered from adverse climatic conditions, and the solar radiation that impacts the plants is modif ied with the purpose of improving their productivity. Therefore, the objective of our study was to evaluate the effect of the material and color of four greenhouse covers over the rate and spectral characteristics of the transmitted radiation, and their relation with chlorophyll content, growth and yield of poblano pepper (Capsicum annuum L.) cv Ébano culture. The study was conducted in four oval shaped macro-tunnels (4 m wide, 2.5 m high and 12 m long). The covers of three macro-tunnels consisted of red, blue and translucent polycarbonate sheets, respectively, and the remaining macro-tunnel cover was high-density diffuse polyethylene. Spectral characteristics of the solar radiation transmitted in each cover were determined using a spectroradiometer. The photosynthetically active radiation (PAR) rate within and outside each macro-tunnel was obtained using quantum sensors. The results of our study showed that plants that grew under polycarbonate covers of different colors presented more chlorophyll content than plants under the high-density polyethylene cover and those from open f ield. Due to the lower rate of PAR and almost null radiation transmissivity from 400 to 570 nm, plants that grew under red polycarbonate sheets were taller and with more foliage, but with lower fruit yield. The highest fruit yield was observed under the translucent polycarbonate and high-density polyethylene covers.